ANALISIS NILAI ABSORBANSI UNTUK MENENTUKAN KADAR FLAVONOID DAUN JARAK MERAH (JATROPHA GOSSYPIFOLIA L.) MENGGUNAKAN SPEKTROFOTOMETER UV-VIS - Ahriani Ahriani; Sri Zelviani; Hernawati Hernawati; Fitriyanti Fitriyanti (JFT : Jurnal Fisika dan Terapannya, 2021)
Research on Absorbance Value Analysis on Determination of Flavonoid Levels in Red Jatropha Leaves (Jatropha Gossypifolia L.) using UV-Vis Spectrophotometer has been conducted. This study aimed to determine the absorbance of red jatropha (Jatropha Gossypifolia L.) leaves on young and old leaves and to determine the flavonoid content of red jatropha (Jatropha Gossypifolia L.) leaves on young and old leaves. The sample used in this study was 200 g of red jatropha leaf powder (Jatropha Gossypifolia L.) with the addition of 2000 ml of 70% ethanol as solvent in a ratio of 1:10. The extraction method used in this study is the MAE (Microwave Assisted Extraction) method to measure the absorbance value of the sample at a wavelength of 436 nm using a UV-Vis spectrophotometer. The results showed that the absorbance value of red jatropha (Jatropha Gossypifolia L.) leaves on young leaves was smaller than on old leaves. Where the absorbance value in young leaves is 0.355 while the absorbance value in old leaves is 0.616. The resulting absorbance value has complied with Lambert-Beer's law (0.2 ≤ A < 0.8). The flavonoid content of red jatropha (Jatropha Gossypifolia L.) leaves in young leaves was lower than in old leaves. Where the levels of flavonoids in young leaves is 2.71% while the levels of flavonoids in old leaves is 4.90%. This shows that the greater the absorbance value, the greater the flavonoid content produced.